In-House Innovative "Diamond Shaped" 3D Printed Microfluidic Devices for Lysozyme-Loaded Liposomes - Federica Sommonte; Edward Weaver; Essyrose Mathew; Nunzio Denora; Dimitrios A. Lamprou (MDPI AG, 2022)
Nanotechnology applications have emerged as one of the most actively researched areas in recent years. As a result, substantial study into nanoparticulate lipidic systems and liposomes (LPs) has been conducted. Regardless of the advantages, various challenges involving traditional manufacturing processes have hampered their expansion. Here, the combination of microfluidic technology (MF) and 3D printing (3DP) digital light processing (DLP) was fruitfully investigated in the creation of novel, previously unexplored "diamond shaped" devices suitable for the production of LPs carrying lysozyme as model drug. Computer-aided design (CAD) software was used designing several MF devices with significantly multiple and diverse geometries. These were printed using a high-performance DLP 3DP, resulting in extremely high-resolution chips that were tested to optimize the experimental condition of MF-based LPs. Monodisperse narrow-sized lysozyme-loaded PEGylated LPs were produced using in-house devices. The developed formulations succumbed to stability tests to determine their consistency, and then an encapsulation efficacy (EE) study was performed, yielding good findings. The in vitro release study indicated that lysozyme-loaded LPs could release up to 93% of the encapsulated cargo within 72 h. Therefore, the proficiency of the association between MF and 3DP was demonstrated, revealing a potential growing synergy.